Pengaruh Penggunaan Nearpod sebagai Media Pembelajaran Interaktif dalam Pembelajaran Bahasa Indonesia - Kanaya Kanaya (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
This research aims to explain the influence of using Nearpod as an Interactive Learning Media in Indonesian Language Learning. Research involving 26 students of the Indonesian Language and Literature Education Program at UIN Syarif Hidayatullah Jakarta showed a positive response to the use of Nearpod as a medium for learning Indonesian. The majority of students were knowledgeable about Nearpod and recognized its positive impact on various aspects of learning. The interactive features, ease of access, and multiple learning modes that Nearpod offers contribute significantly to their learning experience. Overall, the research results confirm that Nearpod has great potential as an effective learning tool to increase students' interactivity and understanding of Indonesian language material.